1993
DOI: 10.1002/eji.1830231010
|View full text |Cite
|
Sign up to set email alerts
|

Murine CD8+ T suppressors against mycobacterial 65‐kDa antigen compete for IL‐2 and show lack of major histocompatibility complex‐imposed restriction specificity in antigen recognition

Abstract: The mechanism of antigen-specific suppression and reasons for aberrant major histocompatibility complex (MHC) class II restriction mediated by CD8+ T cells was investigated in a previously reported murine model of immunosuppression, generated by intraperitoneal priming with Mycobacterium vaccae. Both the CD4+ T helper cells (Th) and CD8+ T suppressor cell (Ts) of M. vaccae-primed mice recognized the 65-kDa antigen of the bacillus, presented by I-A and I-E, respectively. The CD8+ Ts could inhibit non-antigen-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, this competition is greater between T cells specific for the same peptide-MHC complex than for T cells specific for different peptide-MHC complexes (47), and 3A9 and 5CC7 T cells are restricted by different class II Ags. Some have also suggested that T cells may compete for cytokines such as IL-2 (48). Recent work has also demonstrated that recently activated T cells can inhibit the activation of naive T cells in vitro (49).…”
Section: Interactions Between Immune Responses To Concurrent Infectionmentioning
confidence: 99%
“…However, this competition is greater between T cells specific for the same peptide-MHC complex than for T cells specific for different peptide-MHC complexes (47), and 3A9 and 5CC7 T cells are restricted by different class II Ags. Some have also suggested that T cells may compete for cytokines such as IL-2 (48). Recent work has also demonstrated that recently activated T cells can inhibit the activation of naive T cells in vitro (49).…”
Section: Interactions Between Immune Responses To Concurrent Infectionmentioning
confidence: 99%
“…The sonicates of M. vaccae and S. enteritidis and the immunodominant 65-kD antigen of the former were prepared as described earlier [12].…”
Section: Preparation Of Sonicates and Other Test Antigensmentioning
confidence: 99%
“…The antibodies were raised by repeated immunizations with 65-kD antigen of M. vaccae (purified as described earlier [12]), in FIA at 10-day intervals. Rabbit immunization was repeated until a precipitin titre (by agar gel diffusion) of 1:16 was reached.…”
Section: Rabbit and Mouse Anti-65-kd Antibodiesmentioning
confidence: 99%
“…The supernatants were filtered through 0.22m-pore-size membrane filter (Millipore), and their protein content was assayed. The 65-kDa antigen was purified from the sonicate of M. vaccae by preparative agarose isoelectrofocusing, using ampholines (pH range of 3.5 to 5.0) as described earlier (22).…”
mentioning
confidence: 99%